#Stayat home: Social distancing policies and mobility in Latin America and the Caribbean - Daniel Aromi; María Paula Bonel; Julián Cristia; Martín Llada; Juan I. Pereira; Xiomara Pulido; Julieth Santamaria (Inter-American Development Bank (IDB), 2020)
This study examines the impact on human mobility of the national social distancing policies implemented in 18 Latin American and Caribbean countries in March 2020. To do so, it uses georeferenced data from cellular phones and variation between countries with regard to whether these measures were introduced and when. Mobility is measured as the percentage of people traveling more than 1 kilometer per day. Results indicate that lockdowns reduced mobility by an average of 10 percentage points during the 15 days following its implementation. This accounts for a third of the decline in mobility between the first week in March and the first week in April in countries that implemented lockdowns. However, this average effect hides an important heterogeneity. To start with, the impact during the second week of implementation is 28% lower compared to the effect documented during the first week. Also, while lockdowns reduced mobility by between 16 and 19 percentage points in Argentina, Bolivia, and Ecuador, in Paraguay and Venezuela, the reduction was only 3 percentage points. Additionally, we find that school closures reduced mobility by 4 percentage points. Finally, closures of bars and restaurants and cancellation of public events were found to have no impact on the mobility measurement analyzed.
Keywords: C23; H12; I18; 330; Coronavirus; Social distancing; Mobility; Lockdowns